ANALYSIS OF THE EFFECT PERCEIVED EASE OF USE AND PERCEPTION OF RISK ON SURABAYA COMMUNITY'S INTEREST IN PAYING ZIS THROUGH DIGITAL PAYMENT QRIS - Fariid Achmad Wisanggeni; Rachma Indrarini (Lafadz Jaya Publisher, 2023)
This study aims to determine the effect of perceived ease of use and perceived risk on the public interest using the QRIS or the Quick Response Code Indonesian Standard as digital payment for ZIS transactions. The independent variables of this study are perceived ease of use and perceived risk, while the dependent variable is public interest. The data in this study were collected and based on the results of distributing Google Form questionnaires to people who use QRIS for paying ZIS in Surabaya City. This research method uses descriptive quantitative data with a population of as many as 99 respondents. In this study, the classical assumption test and multiple linear regression test through the SPSS 16 application were used as a data analysis tool. The results of this study show that all the variables have influenced each other.